2013
DOI: 10.5560/zna.2012-0101
|View full text |Cite
|
Sign up to set email alerts
|

On the Hydrogen Bonding Structure at the Aqueous Interface of Ammonium-Substituted Mica: A Molecular Dynamics Simulation

Abstract: Dedicated to Professor Alfred Klemm on the occasion of his 100th birthday.Molecular dynamics (MD) computer simulations were performed for an aqueous film of 3 nm thickness adsorbed at the (001) surface of ammonium-substituted muscovite mica. The results provide a detailed picture of the near-surface structure and topological characteristics of the interfacial hydrogen bonding network. The effects of deuterium/hydrogen isotopic substitution in N(H/D) 4 + on the dynamics and consequently on the convergence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
35
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 32 publications
(79 reference statements)
10
35
0
Order By: Relevance
“…[99][100][101] The methods of analysis used here have been previously described in detail. 39,42,50,73 Results and Discussion…”
Section: Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…[99][100][101] The methods of analysis used here have been previously described in detail. 39,42,50,73 Results and Discussion…”
Section: Simulation Detailsmentioning
confidence: 99%
“…This water film is sufficiently thick to characterize both the interfacial features of the structure and the bulk-water behavior in the nano-pores, as demonstrated in previous simulation studies. 39,42,58 Molecular Dynamics (MD) simulations using the statistical NPT (constant N number of atoms, constant pressure P and constant Temperature T) and NVT (constant N number of atoms, constant volume V and constant Temperature T) ensembles were performed using the LAMMPS simulation code. 87 A Nosé-Hoover thermostat and barostat were used to control the temperature and the pressure independently in all 3 dimensions.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent experimental and computational modeling studies have clearly shown that the clay swelling behavior depends strongly on the nature of the charge balancing cation (characterized by the CO2 and H2O solvation energies) and on the composition and location of the permanent structural charge of the clay. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Experimental and computational modeling studies have shown that at reservoir conditions the amount of intercalated CO2 and its structural, dynamical, and energetic properties depend on the basal spacing and the solvation energies of the charge-balancing cation with H2O and CO2 in smectite interlayers under supercritical conditions (scCO2, Tc~31ºC, Pc~73 bar). X-ray diffraction (XRD) studies at pressurized CO2 conditions by Giesting et al 18,19 showed that increase (expansion) of the basal spacing of the common smectite, montmorillonite, depends on the initial interlayer H2O content.…”
Section: Introductionmentioning
confidence: 99%